Seven strategy questions : a simple approach for better execution - Simons, Robert (Boston, Mass. : Harvard Business Review Press, 2010)
This concise guide presents the seven key questions one must regularly explore together: questions on how to organise your company to deliver maximum value to a customer; how do your core values prioritise shareholders; employees and customers; the critical performance variables that you can track; the stategetic boundaries that can be set; how one generates creative tension and the level of committment exhibited.
Includes bibliographical references and index.
opc 08/05/13
Loans
Keywords: Strategic planning; Business planning; Management